The Effect Of Situational Leadership Style, Work Discipline And Work Motivation On Employee Performance At Rantauprapat Syariah Bank Indonesia - Siregar, Nurdalina; Zebua, Yuniman; Nasution, Siti Lam'ah (Publisher Cv. Inara, 2022)
In the midst of the Covid-19 pandemic, Bank Syariah Indonesia Rantauprapat took a number of steps to keep the Bank's business growth healthy. midst of for social distancing due to the Covid-19 pandemic which has been implemented since mid-March 2019, Islamic Banks recorded an increase in the number of transactions through e-channels. This study uses a quantitative approach to determine the effect of situational leadership style, work discipline, and work motivation on employee performance at Bank Syariah Indonesia Rantau Prapat. The results showed that the variables of leadership style, work discipline, and work motivation had a positive and significant effect. This can be seen from the t-value of each independent variable of 4.530, situational leadership style of 4.131, work discipline of 4.131 and work motivation of 3.781, which is greater than the t-table value of 1.696. Then simultaneously also obtained the results of F arithmetic = 6.116 which is greater than the value of F table = 2.68 so that it can be concluded that the independent variable has a positive and significant effect on employee performance.